The Association between Specific Substances of Abuse and Subcortical Intracerebral Hemorrhage Versus Ischemic Lacunar Infarction - Kaplan, Emma H.; Gottesman, Rebecca F.; Llinas, Rafael H.; Marsh, Elisabeth B. (Frontiers in Neurology, 2014)
Background: Hypertension damages small vessels, resulting in both lacunar infarction and subcortical intracerebral hemorrhage (ICH). Substance abuse has also been linked to small vessel pathology. This study explores whether the use of specific substances (eg., cocaine, tobacco) is associated with subcortical ICH over ischemia in hypertensive individuals. Methods: Patients with hypertension, admitted with lacunar infarcts (measuring <2.0cm) or subcortical ICH, were included in analysis. Brain MRIs and head CTs were retrospectively reviewed along with medical records. Demographic information and history of substance use (illicit/controlled: cocaine, heroin, marijuana, benzodiazepines, and methadone; alcohol; and tobacco) was obtained. “Current use” and “history of use” were determined from patient history or a positive toxicology screen. “Heavy use” was defined as: smoking- ≥0.5 packs per day or 10 pack-years; alcohol- average of >1 drink per day (women), >2 drinks per day (men). Logistic regression was performed with ICH as the dependent variable comparing those presenting with ICH to those presenting with ischemia. Results: Of the 580 patients included in analysis, 217 (37%) presented with ICH. The average age was similar between the two groups (64.7 versus 66.3 years). Illicit/controlled drug use was associated with a significantly increased risk of ICH over stroke in unadjusted models (25% versus 15%, p=0.02), with the largest effect seen in users ≥65 years old (not statistically significant). Smoking was associated with ischemia over ICH in a dose-dependent manner: any history of smoking OR 1.84, CI 1.19-2.84; current use OR 2.23, CI 1.37-3.62; heavy use OR 2.48, CI 1.50-4.13. Alcohol use was not preferentially associated with either outcome (p=0.29). Conclusions: In hypertensive patients, tobacco use is associated with an increased risk of subcortical ischemia compared to ICH; while use of illicit/controlled substances appears to be predictive of hemorrhage.